Reformulating Islamic Inheritance Law for Social Media Accounts as Digital Assets: An Empirical Study in Parepare, Indonesia - Poga, Nailah Farafizah; Mutmainnah, Iin; Nur Mizwary Mustamin; Bate, Nurdalia; Rahmawati (Institut Agama Islam Negeri Kendari, 2026)
The rapid expansion of digital life has produced a new inheritance dilemma: social media accounts may outlive their owners as economically productive assets, while legal systems remain unprepared to regulate their posthumous transfer and management. This study aims to formulate an Islamic inheritance law framework for social media accounts as digital assets through a case study in Parepare City, Indonesia. It employs an empirical juridical design with a case-study approach involving 17 purposively selected participants, consisting of 15 influencers, one religious court judge, and one legal academic. Data were collected through semi-structured interviews and questionnaires and analyzed using qualitative content analysis. The findings reveal that social media accounts have developed into economically valuable digital assets through monetization, endorsements, and online commercial activities, and that most participants regard such accounts as inheritable when they have identifiable ownership, measurable economic value, and lawful benefit. The study further finds that the main challenge lies not in the normative legitimacy of inheriting such assets, but in the lack of clear mechanisms for ownership verification, lawful access, managerial authority, privacy protection, and the distribution of continuing economic benefits after death. The discussion shows that Islamic inheritance law is conceptually flexible enough to accommodate these assets through the concepts of al-māl, qiyās, and maqāṣid al-syarī‘ah, but remains operationally underdeveloped in regulating their posthumous management. This study implies the need for normative-technical reform through explicit recognition of economically valuable social media accounts as inheritance objects, clearer distinction between economic rights and access rights, stronger use of digital wills, and a more defined role for religious courts in digital inheritance disputes. Keywords: digital assets; islamic inheritance law; social media accounts.